resolva: 5(2-x)-2(x-1)=3(3x-4)
Soluções para a tarefa
Respondido por
3
5(2-x)-2(x-1)=3(3x-4)
10-5x-2x-2 = 9x-12
5x-2x-9x = -12 -10 + 2
-6x = - 20 . (-1)
6x = 20
x = 20/6
x = 3,333... ou x = 10/3
10-5x-2x-2 = 9x-12
5x-2x-9x = -12 -10 + 2
-6x = - 20 . (-1)
6x = 20
x = 20/6
x = 3,333... ou x = 10/3
Respondido por
6
5(2-x)-2(x-1)=3(3x-4)
10 -5x -2x +2 = 9x -12
-5x -2x -9x = -12 -10 -2
-16x= -24(-1)
+16x= +24
x= 24/16( simplificando por 8), (24:8=3), (16:8=2)
x= 3/2
10 -5x -2x +2 = 9x -12
-5x -2x -9x = -12 -10 -2
-16x= -24(-1)
+16x= +24
x= 24/16( simplificando por 8), (24:8=3), (16:8=2)
x= 3/2
Perguntas interessantes
Matemática,
1 ano atrás
Biologia,
1 ano atrás
Sociologia,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Português,
1 ano atrás